ETHANOL EXTRACT OF MYRMECODIA PENDANS CAUSED HISTOLOGICAL STRUCTURE DAMAGE OF MICE KIDNEY - Manullang, Dini Hilary; Sudira, I Wayan; Berata, I Ketut; Merdana, I Made (Buletin Veteriner Udayana, 2018)
Chemical analysis of the ant-plant ( Myrmecodia pendans ) showed that plants have various chemical compounds of flavonoids, tannins, tocopherols, multimineral and polysaccharides. The aim of this study was to find out the effect of ethanolic extract of ant-plant on histopathological changes in male mice ( Mus musculus ) kidney. Twenty four clinically healthy mice at aged 10-12 with weight 25 to 35 g were obtained for this study. The sample were divided into four groups randomly, each treatment group consisted of six mice. Group P0 is the negative control group were given standard feed and drink, P1 is a group were given standard feed and ethanol extracts ant plant  with a dose of 100 mg/kg body weight, P2 is a group were given standard feed and ethanol extracts ant plant with a dose of 200 mg/kg of body weight, P3 is a group were given standard feed and ethanol extracts ant plant with a dose of 300 mg/kg.  After completion of the treatment on the day, the kidney was taken for histological preparations were made and stained with the hematoxylin-eosin method. The variables examined were haemorrhage, degeneration and necrosis in the renal proximal tubules. The Kruskal-Wallis test results showed that ethanol extract of ant-plant had a significant effect (P?0.05) on the incidence of hemorrhage in the renal tubules. Based on these results it can be concluded that the ethanol extract of ant-plant with a dose of  300 mg/kg body weight can cause kidney histopathological changes such as hemorrhage, degeneration, and necrosis.